Creating effective JavaHelp - Lewis, Kevin (Java series (O'Reilly & Associates), 2000)
Effective, instantly available online help is a requirement for today's interactive applications. Until now, Java application developers have been forced to develop their own help system. That's no longer necessary. With the release of JavaHelpu2122, there is a complete and standard online help system for the Javau2122 platform. Creating Effective JavaHelp covers the main features and options of JavaHelp. It shows how to create a basic JavaHelp system, prepare help topics, and deploy the help system in an application. Written for all levels of Java developers and technical writers, the book takes a chapter-by-chapter approach to building concepts. It imparts a complete understanding of how to create usable JavaHelp systems and integrate them into Java applications and applets. Topics covered include: Understanding JavaHelp Creating your first HelpSet Planning the JavaHelp project Preparing Help topics Creating HelpSet data and navigation files Enhancing the HelpSet Using the JavaHelp API for advanced presentation options Deploying the help system to your users Using third-party help-authoring tools.